Performance of radiofrequency ablation used for metastatic spinal tumor: Numerical approach - Capek, Lukas; Henys, Petr; Barsa, Pavel; Dvorak, Vaclav (Proceedings of the Institution of Mechanical Engineers. Part H, Journal of engineering in medicine, 2017)
Surgical treatment of spine metastases follows only local anatomical and biomechanical objectives. Few cases of actual solitary metastases are rather exceptional, while removal of these metastases and the primary tumor may help to eradicate the process. The aim of our subsequent numerical simulations was to find out the temperature distribution and the volume lesion in a spinal tumor. For this purpose, the parametric three-dimensional numerical model was developed. It was shown that by finite element modeling approach not only the temperature distribution but even the resulted cavity may be estimated. The numerical approach was shown as a strong tool in surgery planning.
Keywords: tumor; Catheter Ablation; Spine; ablation; metastázy nádorů; Finite Element Analysis; Temperature; analýza metodou konečných prvků; nádory páteře; finite element analysis; Neoplasm Metastasis; performance; katetrizační ablace; teplota; Spinal Neoplasms